Antibacterial activity of chrysophsin-3 against oral pathogens and Streptococcus mutans bioﬁlms: Antibacterial activity of chrysophsin-3 - Wang, Kejing; Hou, Lipeng; Sun, Zi-ang; Wang, Wei (Cellular and Molecular Biology, 2022)
Dental caries and pulpal diseases are common oral bacterial infectious diseases, the prevention and treatment of these diseases require the control of the causative pathogens, such as Streptococcus mutans (S. mutans) and Enterococcus faecalis. As a cationic antimicrobial peptide, Chrysophsin-3 has broad-spectrum bactericidal activity against both Gram-positive and Gram-negative bacteria which may cause a variety of oral infectious diseases. The present study evaluated the potential of chrysophsin-3 against several oral pathogens and S.mutans biofilms. The cytotoxic activity of chrysophsin-3 against human gingival fibroblasts (HGFs) was investigated for potential oral application. We use minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and time-kill assay to evaluate the killing effect of chrysophsin-3. Then scanning electron microscopy (SEM) and Transmission Electron Microscope (TEM) were used to analyze the change of morphology and membrane of the pathogens, Live/Dead staining and confocal scanning laser microscopy (CSLM) was used to observe S. mutans biofilms. The results indicate that chrysophsin-3 has varying antimicrobial activities against different oral bacteria. Chrysophsin-3 did not cause obvious cytotoxicity in HGFs at concentrations of 32-128 μg/ml for 5 min or 8 μg/ml for 60 min. SEM revealed membranous blebs and pore formation on the bacterial cell surface, and TEM showed loss of the nucleoid and dissolution of the cytoplasmic space. Furthermore, the CSLM images indicate that chrysophsin-3 can reduce the viability of the cells within the biofilms significantly and had a comparatively lethal effect against S. mutans biofilms. Taken together, our finding suggests that chrysophsin-3 has potential clinical application in oral infectious disease, especially in preventing and treating dental caries.